ANALISIS KINERJA KEUANGAN PT BUKIT ASAM TBK PERIODE 2019-2023 - Ambarwati, Lilik; Purwaningsih, Anis (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study's goal is to analyse PT Bukit Asam Tbk's financial operations from 2019 to 2023 by calculating its profitability, solvency, and liquidity ratios. The data shown is based on second-order statistics from the year that was published by the Indonesian Stock Exchange and PT Bukit Asam Tbk. The analysis method used is deskriptif analysis that focusses on analysing financial indicators. The results of the likuiditas rasio for 2019–2023 are good, meaning that the company has the capacity to pay for its obligations or make payments. Conversely, average or solvability indicates that financial performance in a given year isn't very good, and businesses aren't able to use their assets in the best way possible, indicating that many assets are purchased through trading. Conversely, the debt-to-equity ratio indicates that business operations are quite efficient, with many businesses using large amounts of capital as business tools. Rentability, also known as profitability, indicates that the current business's financial performance is not very good, and that it is not very efficient in generating profits from all of its operational activities.